Linguo-stylistic Devices and Means of Heightening Expressiveness in the Novel “In the First Circle” by Alexander Solzhenitsyn (Linguostylistic Studies, 2020)
The article analyzes the expressive stylistic elements, which add dynamics to narrative description, highlight and emphasize the emotional or aesthetic content in the text of the novel “In the First Circle” by A. Solzhenitsyn. The analysis involves the identification of the main functions of the expressive features in the artistic text and interpretation of them in terms of the functional-stylistic method. The functional-stylistic method is used to study the linguistic means of expressiveness enhancement that characterize the story, in general, and the speech of the characters, in particular. The study has revealed such stylistic techniques and means as the use of phonographical means and dialect vocabulary, repetition, understatement, metaphorical constructions, ironic and paradoxical content, contrast, the unusual syntactic organization of text (exclamation and interrogative constructions, speech devices of impulsivity).The unexpected transitions from one subject’s speech area to another are formally indicated by insertion words, parentheses, and subjective elements as traditional techniques to enhance expression. In the focus of a meticulous study are the examples of irony and paradox that make the reader not only observe the events and objects described but also analyze the mysterious formulas perceived in a different way by each reader. Semantic expressiveness is more related to the expression of the emotions of an individual character, conveyed in his internal monologues or external dialogues.The case study of the article argues that stylistic devices and expressive means like the use of colloquial vocabulary, repetitions of words, understatement, metaphors, irony, paradox, contrast, exclamation, and interrogative structures make the whole artistic text more expressive and, particularly, the characters' speech.
Keywords: dialogue,; monologue,; expressiveness,; metaphorical construction,; contrast,; paradox.